(untitled) - Prof. em. Dr. Heinrich Reinermann †; Prof. Dr. Veith Mehde (geschäftsführend), Leibniz-Universität Hannover; Prof. Dr. Tino Schuppan, Hochschule der Bundesagentur für Arbeit, Schwerin (VM Verwaltung & Management, 2023)
From a practical and academic point of view the journal Verwaltung und Management (VM) contains reports about leadership and management, public service, structures and procedures, human resources development, IT in administration, IT systems, public finance, budget and accounting systems. It provides a professional forum for mutual exchange of ideas and experience to enhance efficiency and productivity in the public sector. This journal addresses leaders and scholars in administration, social scientists, consultants, IT system houses and education centers. Website: www.vum.nomos.de